A-D Typology of TV Viewers - Kotrc, Daniel (Communications - Scientific letters of the University of Zilina, 2007)
We can distinguish the types of TV viewers in quantitative (capacity of viewing) and qualitative (activity/passive) aspects, and their synthesis (A-D types of TV viewers). We documented the dominance of television and radio in cares of 595 adolescent respondents. Practical possibility of using of A-D TV viewers types (and differentiation of TV viewers by capacity of viewing or their activity/passive) has approved.